S.Uvarov’s Imperial Ideology as a Principle of Modernization of the Educational Environment - Bevzіuk, Ye. (Український історичний журнал, 2021)
The purpose of the study. The relevance of the topic has been caused by the fact, that
for many years researches on S.Uvarov’s ideological heritage were done mainly within the Marxist
paradigm from the standpoint of social and class competition. The Soviet historical science argued
that imperial education had served the interests of autocracy, therefore it had adopted the idea of
Official Nationality. At the same time, historians quite carefully omitted the fact that S.Uvarov
had laid the ideological tool for organising the linguistic and cultural assimilation of the peoples of
the Russian Empire. Scientific novelty. There has recently been a tendency to study a complicated
bureaucratic and intellectual heritage of S.Uvarov. Such attention has been related to a growing
interest of contemporaries in the philosophy of conservatism with the intensification of national
processes. The purpose of the research is to clarify the content and objectives of S.Uvarov’s
conservative and ideological doctrine, which became “an intellectual weapon” of modernisation of
the educational sphere and part of the domestic imperial national policy. The object of research is
the ideological system of the Russian autocracy, the subject is S.Uvarov’s intellectual heritage, and
specifically his programme of Official Nationality, which provided an algorithm for “evolutionary”
correlation of the ideological foundation of the Russian educational environment for many years.
Conclusion. Hence, S.Uvarov took his place in the history of the empire not just as a talented
bureaucrat and reformer of the educational environment, but as a politician who tried to emancipate
the Russian national consciousness against the background of the imperial ideology, in the key of
loyalty to the autocracy. His Triad served the purpose of ideologising society in order to maintain
control over the public. S.Uvarov’s proclamation of the Official Nationality programme contrasted
the uncontrolled spread of materialistic and liberal ideas with a conscious conservative barrier in the
form of strengthening bureaucratic regulation in the sphere of education. Within the framework of
the domestic policy of state nationalism, the minister combined public education with “the spirit
of Orthodoxy, Autocracy and Nationality”. Мета дослідження спрямована на з’ясування змісту і завдань уваровської
консервативно-ідеологічної доктрини, що стала «інтелектуальною зброєю» модернізації
освітньої сфери та частиною внутрішньої імперської національної політики. Об’єктом
дослідження є ідеологічна система російського самодержавства, предметом – інтелектуальна
спадщина С.Уварова, а конкретно його програма «офіційної народності», яка на багато
років забезпечила алгоритм «еволюційної» кореляції ідеологічного фундаменту російського
освітнього середовища. Методологія спирається на принципи історизму, системності та
цивілізаційної теорії розвитку соціумів. Такий підхід дозволяє об’єктивно й неупереджено
висвітлити реформаторську діяльність С.Уварова та визначити імперський зміст його
освітніх реформ. Наукова новизна. Внесок у дослідження інтелектуальної спадщини
С.Уварова полягає не лише в розкритті ідеологічної тріади як цілісної політичної доктрини
самодержавства, котра спиралася на конструкцію російської нації в рамках особливого
православного історико-цивілізаційного типу. Показано, що комплексна система ідей
слугувала меті «емансипації» етнокультурного середовища Наддніпрянської України задля
інкорпорування російської національної ідентичності до освітніх структур колонізованої
периферії. Висновки. С.Уваров посів своє місце в історії імперії не просто як талановитий
бюрократ-реформатор освітнього середовища, а як політик, котрий намагався емансипувати
російську національну свідомість на тлі імперської ідеології у ключі вірнопідданого
ставлення до самодержавства. Проголошена ним програма «офіційної народності»
протиставила неконтрольованому поширенню матеріалістичних і ліберальних ідей свідомий
консервативний бар’єр у формі посилення бюрократичного реґулювання освітньої сфери.
На практиці до системи народної просвіти було закладено ідеологічний інструмент,
що впливав на адміністративну систему самодержавства у плані організації мовної й
культурної асиміляції народів імперії.